2018
DOI: 10.5334/paah.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Foot Pressure between Teenager Girls and Young Female Adults

Abstract: Background: Increase age is one of the main factors influencing spatiotemporal and pressure parameters. Adolescence and young adulthood are unique periods in the life span that present opportunities and challenges in improving health. Meantime, this age span involve significant growth and development. But the previous studies seldom examine the adolescents gait characteristics and pay attention to the plantar pressure changes between this age span. Purpose: Given the complex variation of these transitional age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The less adept lower limb for balance, the greater the inability to provide an optimally stable base for the neuromuscular system to maintain a constant tension. This could promote absorption of increased load and contribute to the instability recorded (Fang, 2018; Plisky et al, 2006; Hewett, Myer & Ford, 2001; Weaver et al, 1999). In addition, Earl & Hertel (2001) showed that the support leg muscles could be activated to a different extent during the SEBT, which could be contributing to postural sway under during continuous table tennis multi-ball training.…”
Section: Discussionmentioning
confidence: 99%
“…The less adept lower limb for balance, the greater the inability to provide an optimally stable base for the neuromuscular system to maintain a constant tension. This could promote absorption of increased load and contribute to the instability recorded (Fang, 2018; Plisky et al, 2006; Hewett, Myer & Ford, 2001; Weaver et al, 1999). In addition, Earl & Hertel (2001) showed that the support leg muscles could be activated to a different extent during the SEBT, which could be contributing to postural sway under during continuous table tennis multi-ball training.…”
Section: Discussionmentioning
confidence: 99%
“…The human foot has to endure the tasks of walking and locomotion through the whole life (Bosch et al, 2009). While walking, plantar pressure is generated while weight bearing is transferred to the supporting leg (Guet al, 2011;Chen et al, 2019;Fang, 2018). Plantar pressures represent a permanent concern due to the risk of foot deformity and as a source of pain (Mei et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among many factors that can influence the foot structure, body weight could be the most significant [7]. Overweight and obese have been shown to negatively affect foot structure causing discomfort for individual particularly among the adolescent [8]. Previous studies have reported a higher incidence of foot arch changes in growing females [9].…”
Section: Introductionmentioning
confidence: 99%